Tongguan Capsule Mitigates Post-myocardial Infarction Remodeling by Promoting Autophagy and Inhibiting Apoptosis: Role of Sirt1 - Mao, Shuai; Chen, Peipei; Li, Ting; Guo, Liheng; Zhang, Minzhou (Frontiers in Physiology, 2018)
Left ventricular (LV) adverse remodeling and the concomitant functional deterioration contributes to the poor prognosis of patients with myocardial infarction (MI). Thus, a more effective treatment strategy is needed. Tongguan capsule (TGC), a patented Chinese medicine, has been shown to be cardioprotective in both humans and animals following ischemic injury, although its precise mechanism remains unclear. To investigate whether TGC can improve cardiac remodeling in the post-infarct heart, adult C57/BL6 mice underwent coronary artery ligation and were administered TGC or vehicle (saline) for 6 weeks. The results demonstrated that the TGC group showed significant improvement in survival ratio and cardiac function and structure as compared to the vehicle group. Histological and western blot analyses revealed decreased cellular inflammation and apoptosis in cardiomyocytes of the TGC group. Furthermore, TGC upregulated the Atg5 expression and LC3II-to-LC3I ratio but downregulated autophagy adaptor p62 expression, suggesting that TGC led to increased autophagic flux. Interestingly, with the administration of 3-methyladenine, an autophagy inhibitor, in conjunction with TGC, the aforesaid effects significantly decreased. Further mechanistic studies revealed that TGC increased silent information regulator 1 (Sirt1) expression to reduce the phosphorylation of the mammalian target of rapamycin and its downstream effectors P70S6K and 4EBP1. Moreover, the induction of Sirt1 by TGC was inhibited by the specific inhibitor EX527. In the presence of EX527, TGC-induced autophagy-specific proteins were downregulated, while apoptotic and inflammatory factors were upregulated. In summary, our results demonstrate that TGC improved cardiac remodeling in a murine model of MI by preventing cardiomyocytes inflammation and apoptosis but enhancing autophagy through Sirt1 activation.